Peri-orbital lymphangioma treated by lymphatic-venous anastomosis with indocyanine green lymphography analysis - Motoi Kato, M.D; Shoji Watanabe, M.D. PhD; Takuya Iida, M.D. PhD; Azusa Watanabe, M.D. PhD; Furuya Megumi, M.D (Elsevier, 2017)
Lymphatic malformation (LM), also known as lymphangioma, is a rare condition that can occur anywhere in the body in adults and children. LM, especially micro-cystic type, consists of multiple clustering skin/subcutaneous cysts that may involve deeper functional tissue. Although LM is generally benign, it may cause serious location-dependent problems. Periorbital LM, for example, often causes facial disfigurement and visual impairment. Especially, micro-cystic type of lymphatic malformation (mLM), is a challenging condition to treat. Currently available therapies for mLM have limited effectiveness and carry a high risk of complications. Thus, it is necessary to develop a novel treatment for mLM that is less invasive and highly effective. There has been a question of the exact location and direction of lymphatic flow into, within, and out of LM. There were some reports investigating the intra-cystic flow of LM; however, only a few focused on the afferent and efferent lymphatic flow of LM. With our detailed study using lymphography, we were able to determine the lymphatic flow pattern in periorbital LM, which was large enough to perform lymphatic venous anastomosis (LVA). LVA is a surgically-placed bypass between afferent collecting lymphatic vessels and veins, which in our study resulted in decreasing both the influx and the total volume of lymph in the LM. To our knowledge, this is the first study of Indocyanine green (ICG) lymphography on mLM, and LVA for its treatment. Here we present our case of periorbital mLM with LVA and discuss its less invasive surgical strategy.